Prevalence of Specific Antibodies to Chlamydia pneumoniae in Korea - Choi, Tae Yeal (American Society for Microbiology, 1998)
To clarify the endemic status of Chlamydia pneumoniae in Korea, the incidence of antibodies in 564 serum samples from healthy individuals, patients with respiratory infection, and cord blood specimens was evaluated. We conclude that C. pneumoniae infection is highly endemic in Korea and that this infection is associated with acute respiratory diseases.